A new family of generalized parallel manipulators with configurable moving platforms. (November 2020) - Tian, Chunxu; Zhang, Dan
Highlights: A novel method for synthesizing GPMs with configurable moving platforms. Five closed-loop configurable platforms with integrated end-effectors. The serial limbs and the redundantly actuated hybrid limbs are enumerated. The relationships among all kinds of limbs are revealed. A novel family of 4/5/6-DOF GPMs with configurable platforms is presented. Abstract: A Conventional Parallel Manipulator (CPM) usually uses a rigid moving platform as the end-effector to connect serial legs. Since serial legs independently support the platform, kinematic joints are embedded into the rigid moving platform. However, the moving platforms of Generalized Parallel Manipulators (GPMs) are not limited to rigid bodies. The introduction of configurable platforms with integrated end-effectors allows for providing a multipoint connection with the environment. As a result, the functionality of parallel manipulators can be further extended. Resulting from the property of the platform, a significant challenge of connecting moving platforms with serial limbs is posed. This paper puts forward a systematic method for synthesizing parallel manipulators with configurable platforms. To realize the cooperation of the integrated end-effectors, the multi-drive hybrid limbs are designed base on the screw theory. According to the constraint synthesis method, a novel class of parallel manipulators with configurable platforms is constructed. Then the examples with different motion patterns are offered to corroborate the effectiveness of the proposed method. At last, driving schemes and the potential applications of the derived manipulators are discussed.